2011
DOI: 10.1104/pp.111.175372
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Integrity Controls Root Elongation via a General 1-Aminocyclopropane-1-Carboxylic Acid-Dependent, Ethylene-Independent Pathway  

Abstract: Cell expansion in plants requires cell wall biosynthesis and rearrangement. During periods of rapid elongation, such as during the growth of etiolated hypocotyls and primary root tips, cells respond dramatically to perturbation of either of these processes. There is growing evidence that this response is initiated by a cell wall integrity-sensing mechanism and dedicated signaling pathway rather than being an inevitable consequence of lost structural integrity. However, the existence of such a pathway in root t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 54 publications
6
150
1
3
Order By: Relevance
“…The immediate ethylene biosynthesis precursor ACC has recently been suggested to play an ethyleneindependent biological role in plants (Tsang et al, 2011). However, the direct application of ethylene gas to wildtype and ein2-5 mutant plants in our experiments still resulted in a decrease in both the Ser-62-dephosphorylated isoform of ERF110 (Li et al, 2012) and kinase activity (or increased phosphatase activity) toward Ser-62 of ERF110 (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…The immediate ethylene biosynthesis precursor ACC has recently been suggested to play an ethyleneindependent biological role in plants (Tsang et al, 2011). However, the direct application of ethylene gas to wildtype and ein2-5 mutant plants in our experiments still resulted in a decrease in both the Ser-62-dephosphorylated isoform of ERF110 (Li et al, 2012) and kinase activity (or increased phosphatase activity) toward Ser-62 of ERF110 (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…5,6 In addition, reduced root cell elongation and aberrant cell expansion are observed in the cobra mutant deficient in cellulose microfibril organization 7 or roots grown in the presence of isoxaben, a cellulose synthase inhibitor. 8 These observations raise the possibility that the rss3 mutant has a defect in the cell wall.…”
mentioning
confidence: 91%
“…Nonetheless, severe effects on seedling root growth should be expected for all of these inhibitors of ethylene synthesis, because reduced ethylene synthesis appears to be a primary defect in PLP-deficient roots, leading to impairments in auxin synthesis and distribution and in apical meristem function (Boycheva et al, 2015). Intriguingly, genetic analysis revealed an essential embryonic requirement for ACS function (but not ethylene signaling) in Arabidopsis (Arabidopsis thaliana; Tsuchisaka et al, 2009), and additional work has suggested that ACC may act in an ethylene-independent mode to signal loss of cell wall integrity (Xu et al, 2008;Tsang et al, 2011).…”
Section: Hardware Of the Biosynthetic Pathwaymentioning
confidence: 99%